Leave your mess at home - Akinola, Tolani (Pamela Dorman Books / Viking, 2026)
"A warm, funny and tender debut about the uncomfortable, unbreakable ties of family as four adult siblings come home to confront the state of their own lives and each other The Longe siblings are really botching their parents' American Dream. Sola Longe, eldest daughter, estranged from the family, is secretly back home in Chicago for the first time in a decade. She's a newly single and recently disgraced influencer trying to quietly put her life back together again. But Sola's unexpected return sets her on a crash course toward her other three adult siblings. And when the four of them finally find themselves together again at their Nigerian immigrant parents' Thanksgiving table, a decade's worth of secrets and a lifetime of resentments explode to the fore. But Sola is not the only Longe whose life is a total mess. The other three aren't doing much better: Anjola is in love with her best friend, who just got engaged to someone else; Karen, a college junior and the youngest, is grappling with her sexuality and self-image; and Ola, the golden child with his own baby on the way, is questioning his marriage and how to raise a Black son in America. In the wreckage of their fateful reunion, each Longe is forced to reckon with the past, take stock of what really matters, and find a way back to each other. Big-hearted, hilarious, and poignant, Leave Your Mess At Home is an insightful debut about forgiveness, unconditional love, and becoming who you want to be. It's a novel that asks: what do we owe to our families, and what do we owe to ourselves?"-- Provided by publisher.